UPAYA PENINGKATAN HASIL BELAJAR EKONOMI PADA SISWA KELAS X AKUNTANSI 1 SMK NEGERI 1 PEKANBARU MELALUI PEMBELAJARAN KOOPERATIF TIPE TPS (THINK PAIR SHARE) TAHUN AJARAN 2018 - Atlas, Bambang (JGK (Jurnal Guru Kita), 2021)
Abstract: Efforts to Improve Economic Learning Outcomes in Class X Accounting 1 SMK Negeri 1 Pekanbaru Through Cooperative Learning Type Tps (Think Pair Share) Academic Year 2018. This study aims to improve economic learning outcomes in students of Class X Accounting 1 SMK Negeri 1 Pekanbaru by applying cooperative learning type TPS (Think Pair Share). The formulation of the problem from this research is whether the application of Think Pair Share (TPS) cooperative learning can improve economic learning outcomes in students of Class X Accounting 1 SMK Negeri 1 Pekanbaru in the 2018 academic year? The subjects of this study were students of Class X Accounting 1 consisting of 36 students with a composition of 30 female students and 6 male students. This is supported by the following facts: 1) Student activity in apperception increased by 14 %. These results are shown in cycle 1 by 58% (11 students) and in cycle 2 by 72% (19 students). 2) The activeness of students in participating in TPS type cooperative learning increased by 16%. These results are shown in the first cycle of 61% (16 students) and in the second cycle of 77% (19 students). 3) The activeness of students in pair/group discussions increased by 20%. These results are shown in the first cycle of 61% (16 students) and in the second cycle of 81% (19 students). 4) Completeness of learning outcomes increased by 15%. These results are shown in the first cycle of 68% (16 students) and in the second cycle of 83% (19 students). 5) The activeness of students in discussions experienced the greatest increase compared to the activeness and completeness of other students’ learning outcomes. Keywords: Economic Learning Outcomes, TPS Type Cooperative Learning (Think Abstrak: Upaya Peningkatan Hasil Belajar Ekonomi Pada Siswa Kelas X Akuntansi 1 SMK Negeri 1 Pekanbaru Melalui Pembelajaran Kooperatif Tipe Tps (Think Pair Share) Tahun Ajaran 2018. Penelitian ini bertujuan untuk meningkatkan hasil belajar ekonomi pada siswa Kelas X Akuntansi 1 SMK Negeri 1 Pekanbaru dengan menerapkan pembelajaran kooperatif tipeTPS (Think Pair Share). Rumusan masalah dari penelitian ini adalah apakah penerapan pembelajaran kooperatif tipe Think Pair Share (TPS) dapat meningkatkan hasil belajar Ekonomi pada siswa Kelas X Akuntansi 1 SMK Negeri 1 Pekanbaru tahun pelajaran 2018 ? Yang menjadi subjek dari penelitian ini adalah siswa Kelas X Akuntansi 1 yang terdiri dari 36 siswa dengan komposisi 30 orang siswa Perempuan dan 6 orang siswa Laki-laki.Hal tersebut didukung oleh fakta-fakta sebagai berikut: 1) Keaktifan siswa dalam apersepsi meningkat sebanyak 14%. Hasil tersebut ditunjukkan pada siklus 1 sebesar 58% (11 siswa) dan pada siklus 2 sebesar 72% (19 siswa). 2) Keaktifan siswa dalam mengikuti pembelajaran kooperatif tipe TPS meningkat sebanyak 16%. Hasil tersebut ditunjukkan pada siklus 1 sebesar 61% (16 siswa) dan pada siklus 2 sebesar 77% (19 siswa). 3) Keaktifan siswa dalam diskusi berpasangan/ kelompok meningkat sebanyak 20%. Hasil tersebut ditunjukkan pada siklus 1 sebesar 61% (16 siswa) dan pada siklus 2 sebesar 81% (19 siswa). 4) Ketuntasan hasil belajar meningkat sebesar 15%. Hasil tersebut ditunjukkan pada siklus 1 sebesar 68% (16 siswa) dan pada siklus 2 sebesar 83% (19 siswa). 5) Keaktifan siswa dalam diskusi mengalami peningkatan terbesar dibandingkan dengan keaktifan dan ketuntasan hasil belajar siswa lainnya. Kata Kunci: Hasil Belajar Ekonomi, Pembelajaran Koooperatif Tipe TPS (Think Pair Share)